Phase 2 Dose-Finding Study in Patients with Gout Using SEL-212, a Novel PEGylated Uricase (SEL-037) Combined with Tolerogenic Nanoparticles (SEL-110) - Alan Kivitz; Wesley DeHaan; Rehan Azeem; Justin Park; Sheri Rhodes; Jamie Inshaw; Sheldon S. Leung; Savvas Nicolaou; Lloyd Johnston; Takashi K. Kishimoto; Peter G. Traber; Earl Sands; et al. (Rheumatology and Therapy, 2023)
Abstract Introduction SEL-212 is a developmental treatment for uncontrolled gout characterized by serum uric acid (sUA) levels ≥ 6 mg/dl despite treatment. It comprises a novel PEGylated uricase (SEL-037; also called pegadricase) co-administered with tolerogenic nanoparticles containing sirolimus (rapamycin) (SEL-110; also called ImmTOR®), which mitigates the formation of anti-drug antibodies (ADAs) against uricase and SEL-037 (PEGylated uricase), thereby enabling sustained sUA control (sUA < 6 mg/dl). The aim of this study was to identify appropriate dosing for SEL-037 and SEL-110 for use in phase 3 clinical trials. Methods This open-label phase 2 study was conducted in adults with symptomatic gout and sUA ≥ 6 mg/dl. Participants received five monthly infusions of SEL-037 (0.2 or 0.4 mg/kg) alone or in combination with three or five monthly infusions of SEL-110 (0.05–0.15 mg/kg). Safety, tolerability, sUA, ADAs, and tophi were monitored for 6 months. Results A total of 152 adults completed the study. SEL-037 alone resulted in rapid sUA reductions that were not sustained beyond 30 days in most participants due to ADA formation and loss of uricase activity. Levels of ADAs decreased with increasing doses of SEL-110 up to 0.1 mg/kg, with anti-uricase titers < 1080 correlating with sustained sUA control and reductions in tophi. Overall, 66% of evaluable participants achieved sUA control at week 20 following five monthly doses of SEL-037 0.2 mg/kg + SEL-110 0.1–0.15 mg/kg, whereas only 26% achieved sUA control at week 20 when SEL-110 was withdrawn after week 12. Compared to other dose combinations, SEL-037 0.2 mg/kg + SEL-110 0.15 mg/kg achieved the greatest sUA control at week 12 and was well-tolerated with no safety concerns. Conclusion Results provide continued support for the use of multiple monthly administrations of SEL-037 0.2 mg/kg + SEL-110 0.1-0.15 mg/kg in clinical trials for SEL-212. Trial Registration ClinicalTrials.gov identifier, NCT02959918.